Adverse event profiles of selpercatinib: a real-world pharmacovigilance analysis based on FAERS database - Jiancheng Qian; Shuohan Zhang; Cheng Jiang (BMC Cancer)
Abstract Background Selpercatinib, a highly selective tyrosine kinase inhibitor, has emerged as an excellent treatment option for patients with rearranged during transfection-altered cancer. However, there is limited comprehensive safety information available for selpercatinib through large-scale post-marketing monitoring. Methods This study conducted a comprehensive analysis of selpercatinib-related adverse events (AEs) using the FDA Adverse Event Reporting System database. Four disproportionality methods were employed to identify potential AEs associated with selpercatinib. Specifically, this study investigated the differences in AEs of selpercatinib with respect to reporter continent, indication, sex, age, weight, dose, frequency, and onset time. Results A total of 464 reports and 1,007 selpercatinib-related AEs were identified. Three new significant AEs were discovered, including dysphagia, pericardial effusion, and hemiparesis. Notably, Asia reported hepatic function abnormal more frequently, especially in patient administered doses exceeding 160 mg. Furthermore, hypersensitivity was reported more frequently by Asia and in individuals weighing less than 50 kg. Conclusions It is paramount to stay vigilant concerning the potential emergence of three newly identified AEs. Significant differences were found in selpercatinib-related AEs concerning reporter continent, sex, weight, dose, frequency, and onset time, which deserved clinical attention. These findings contribute to a broader understanding of the AE profiles of selpercatinib.